2019
DOI: 10.53555/eijas.v5i4.111
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Azospirillum Brasilense Under Different Moisture Content Levels

Abstract: The survival and proliferation of free and alginate immobilized, Azospirillum brasilense in a bulk soil collected from Derna region at different moisture content levels (10%, 40% and 60 %). A reduction of cell number in the experimental units (sterile or non-sterile soil) for all the tested moisture levels was observed after 15 days after the inoculation. Nevertheless, different parameters among the level of moisture content could be observed in the reduction of the population .soil-sterilization did not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…Therefore, an increase in the Azospirillum population with an increase in moisture content (maintained through supplemental irrigation prior to collection of rhizosphere soil samples) was observed in the present study. The same results were reported by Belaid et al [93], who observed that when the moisture content increased, the Azospirillum population increased over time.…”
Section: Microbial Populationsupporting
confidence: 89%
“…Therefore, an increase in the Azospirillum population with an increase in moisture content (maintained through supplemental irrigation prior to collection of rhizosphere soil samples) was observed in the present study. The same results were reported by Belaid et al [93], who observed that when the moisture content increased, the Azospirillum population increased over time.…”
Section: Microbial Populationsupporting
confidence: 89%
“…So, an increase in the Azospirlium population with an increase in moisture content (maintained through supplemental irrigation prior collection of rhizosphere soil samples) was noticed in the current experiment. The same results were reported by Belaid et al [93] who observed that when moisture content was increased, there was an increase in the Azospirillum population along with time.…”
Section: Microbial Populationsupporting
confidence: 88%
“…It was found that the PIA formulation had a higher moisture content than the alginate sample, likely due to PIA being more hydrophilic. There have been several reports which support the impact of residual moisture in improving microbial survival in microcapsules. …”
Section: Results and Discussionmentioning
confidence: 99%